Optimasi Level of Detail dan Occlusion Culling dalam Game Aaron Lost in the Jungle - Simatupang, Frans Anderson; Amalia Purnamasari, Dwi (Politeknik Negeri Batam, 2024)
This research analyzes the effectiveness of Culling Occlusion optimization techniques andLevel of Detail (LOD) optimization techniques in improving the performance of non-optimized 3D games.optimized. Using quantitative research methods with an experimental approach.experimental approach. Culling Occlusion is a technique that hides objects that are not visible to the player.that are not visible to the player, while LOD is a technique thatLOD is a technique that displays a version of the object with reduced detail based on the distanceThe results show that by using the LOD technique managed to increase the FPS by 107%, while using theOcclusion Culling technique only marginally improved by 19%. This finding indicates that while both techniques are effective in optimizing performance, the LOD technique provides aboth techniques are effective in optimizing performance, the LOD technique provides a more significant improvementmore significant.